2017
DOI: 10.1113/jp273735
|View full text |Cite
|
Sign up to set email alerts
|

Low pHoboosts burst firing and catecholamine release by blocking TASK‐1 and BK channels while preserving Cav1 channels in mouse chromaffin cells

Abstract: Mouse chromaffin cells (MCCs) generate action potential (AP) firing that regulates the Ca -dependent release of catecholamines (CAs). Recent findings indicate that MCCs possess a variety of spontaneous firing modes that span from the common 'tonic-irregular' to the less frequent 'burst' firing. This latter is evident in a small fraction of MCCs but occurs regularly when Nav1.3/1.7 channels are made less available or when the Slo1β2-subunit responsible for BK channel inactivation is deleted. Burst firing causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 64 publications
7
55
2
Order By: Relevance
“…It has been reported that blood pH decreases to pH 6.9 when top athletes are maximally exercised (15). Thus, the present and the Guarina et al (17) findings indicate that TASK channels have an essential role for acidic detection in AM cells under physiologic conditions, such as exercise.…”
Section: Discussion K + Channels Involved In the Resting Membrane Potsupporting
confidence: 69%
See 1 more Smart Citation
“…It has been reported that blood pH decreases to pH 6.9 when top athletes are maximally exercised (15). Thus, the present and the Guarina et al (17) findings indicate that TASK channels have an essential role for acidic detection in AM cells under physiologic conditions, such as exercise.…”
Section: Discussion K + Channels Involved In the Resting Membrane Potsupporting
confidence: 69%
“…Therefore, the molecular identity of TASK1-like channels in AM cells is indispensable in elucidating how the endocrine functions of AM cells are defined. In addition, besides TASK channels, large-conductance Ca 2+ -dependent K + (BK) channels have recently been suggested to be involved in pH decreaseinduced excitation in mouse AM cells (17). Thus, the present experiments were aimed at clarifying the involvement of BK channels in acidity-induced excitation and elucidating the molecular identity of TASK channels in mouse AM cells by using the genetic deletion of TASK channels.…”
mentioning
confidence: 99%
“…; Guarina et al . ). BK currents were obtained by first determining the contribution of K V currents to the total by adding 1 μM paxilline to block BK channels (Zhou & Lingle, ).…”
Section: Resultsmentioning
confidence: 97%
“… a , b ; Guarina et al . ; for a review see Lingle et al . ), specifically when (1) Na V channels are steadily inactivated, (2) K + ‐permeable channels (BK, TASK1‐3) are blocked, (3) inward L‐type currents are increased, or (4) following deletion of the BK‐β 2 subunit that completely abolishes BK channel inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation